Avaliação da rugosidade superficial da cerâmica de dissilicato de lítio processada por injeção e CAD/CAM após polimento com kits intraorais - Pereira, Carlos Henrique Ribeiro (2019)
Technological advances make it possible for the dentist to work with new restorative materials. Among these, lithium disilicate ceramics are an excellent choice for minimally invasive aesthetic restorations, as well as restoration of function through full crowns and conventional fixed prothesis and over implants, and can be processed by injection or by prefabricated block milling (CAD/CAM). However, due to the low mechanical strength of lithium disilicate before its adhesion to the dental structure, occlusal adjustments are indicated after cementation, and this wear can cause inconveniences such as facilitating biofilm retention, reduced mechanical strength, higher ceramic abrasiveness against antagonist tooth enamel and others biological and mechanical complications. Intraoral polishing materials are also evolving, promising to return surface smoothness and gloss that were lost after such wear, however, there is little evidence of their effectiveness in material processed by different techniques. Due to the lack of scientific basis in the literature, the objective of this study is to evaluate the surface roughness of lithium disilicate ceramics processed by two techniques (injection and CAD/CAM) after simulating occlusal wear and polishing with two intraoral kits. For this purpose, 78 lithium disilicate specimens (10mm diameter X 2mm height) were manufactured in the laboratory (n = 39 injected and n = 39 CAD/CAM), divided into six groups: G1: injected control (glaze); G2: injected Edenta polishing; G3: injected DhPro polishing; G4: control milling (glaze); G5: milled Edenta polishing; G6: Milled DhPro polishing. For reading the average 3D roughness (Sa -μm) the uncontacted optical profilometer (CCI MP, Taylor Hobson. Leicester, England) was used using 0.08mm cutoff, 50x lens, with a reading area of 0.16mm, velocity 1x read, in XYZ resolution mode; each specimen was read in three distinct areas (central region, 3mm left and 3mm right) and obtained an average. A first reading (baseline) was performed of all specimens (Sa1), after which the groups G2, G3, G5 and G6 had their surface worn for 10 seconds with 3099 F high-rotation diamond tip under cooling (KG Sorensen, S. Paulo, Brazil), were washed in an ultrasonic vat (L100, Shuster, Rio Grande do Sul, Brazil) for 480 seconds and a new reading was performed (Sa2). Then, in groups G2 and G5, polishing was performed with the Edenta intraoral kit (St. Margrethen, Switzerland) and in groups G3 and G6 with the DhPro intraoral kit (Paraná, Brazil). After polishing, the specimens were again washed in an ultrasonic vat for 480 seconds, and a third reading (Sa3) was performed in all groups. Mean roughness (Sa μm) was evaluated by the parametric 3-way repeated measures ANOVA test and Tukey test, with the factors Processing method, Polishing method and Time, with significance of 1% (α = 0.01). The results showed that all factors studied (Processing method, Polishing method and Time), and their interactions, affected the roughness of the materials studied (p <0.01). Glaze promoted the lowest Sa values in relation to other surface treatments (p <0.001), but without differences in relation to the ceramic processing method (p> 0.01). Occlusal adjustment promoted higher Sa values for the injected ceramics, different from those processed by CAD/CAM (p <0.01). Polishing with DhPro kit promoted lower roughness value when compared to Edenta kit (p <0.001), with lower values in CAD/CAM processed ceramics compared to pressed (p <0.001), but polishing methods showed values of roughness higher than glaze (p <0.001). Thus, it can be concluded that intraoral polishers are a good option to reduce the roughness caused by occlusal adjustments, promoting values lower than clinically acceptable parameters, but significantly higher than those promoted by laboratory glaze.